Relationships between intercultural sensitivity and educational context: thematic fields (2023)
This communication is situated in the domain of Science Education with an Intercultural Approach and aims to establish thematic areas that have emerged from currents studying Intercultural Sensitivity focused on the educational context. The methodology used is based on Bibliographic Information Mapping, where 101 articles were retrieved from databases such as Redylac, Eryc, Dialnet, and Scopus. Nine thematic areas associated with Intercultural Sensitivity in education emerge from this. The works found date from 2001 to 2022, with a significant growth in Latin America, North America, and Europe. Furthermore, there is a significant contribution in the fields of Adaptation and Intercultural Dialogue. It is concluded that the retrieved works provide alternatives that contribute from current educational settings to intercultural scientific education by identifying of relationships between cultures, which are mediated by the development of intercultural competencies that enhance and expand areas of contact with the other.